Mathematical Analysis of Supply Chain Implementation on Indian Automotive Sector: An Information Communication based Approach - Chandak, Sumit; Chandak , Amit (E-COMMERCE FOR FUTURE & TRENDS, 2022)
Technology is rapidly and continually evolving. Implementation of e-business processes (EBPR) within supply chain practices is required in order to maximize revenue and customer satisfaction. Adoption of technical instruments in information technology (IT) inside the supply-chain process (SCP) is necessary to acquire competitive advantages. In order to obtain a competitive advantage, supply chain professionals must use cutting-edge technologies. Supply chain managers are now under pressure in every industry to increase profits and please customers. As a consequence, supply chain managers can improve supply chain performance and gain a competitive edge by implementing ebusiness operations and IT tools. Adoption of IT tools improves supply chain performance (SCPR), and also client satisfaction and SCP costs. Due to the cost savings, the product could be provided to clients at a fair price. India’s automobile industry has been steadily expanding for the past two decades, but is also confronting increasing worldwide competition. As a result, in order to compete globally, they must offer products at a fair price that are of high quality. Implementing e-business processes in SCP will boost SCPR and give Indian automobile manufacturers a competitive advantage (IAI). Companies may readily obtain the most up-to-date information within SP thanks to the use of IT tools. This research examines how EBPR affects SCPR in the context of IAI. As an independent variable, increase in operational excellence, inventory control, logistics, supply chain, and supply chain are tested.